Legal features of use and protection of agricultural land in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The concept, types, forms and rules of legal regulation of agricultural land are set out in the Land code of the Republic of Kazakhstan of 20 June 2003. Article 97 of the Land code of the Republic of Kazakhstan establishes agricultural land as land provided for or intended for agricultural purposes. This is the most basic category of land from the categories of land, the main feature of which is that the Land is the main means for industrial raw materials and feed needed for humans and animals. In General, agricultural land is the most favorable, fertile land in comparison with other categories of land of the Republic of Kazakhstan, subject to special protection (information and legal system of justice, 2017). In General, agriculture is the oldest of all branches of economy and directly depends on the state of nature. In addition, agriculture is the most common industry. Indeed, at present there is no state that is not engaged in various sectors of agriculture. In the house of scientists, approximately 50 species secrete. According to data, in the world about 1.3 billion people work in this industry, including peasant families in agriculture, this figure reaches 2.6 billion people.